2012
DOI: 10.5487/tr.2012.28.3.165
|View full text |Cite
|
Sign up to set email alerts
|

Effects of White Radish (Raphanus sativus) Enzyme Extract on Hepatotoxicity

Abstract: Raphanus sativus (Cruciferaceae), commonly known as radish is widely available throughout the world. From antiquity it has been used in folk medicine as a natural drug against many toxicants. The present study was designed to evaluate the hepatoprotective activity of radish (Raphanus sativus) enzyme extract (REE) in vitro and in vivo test. The IC50 values of REE in human liver derived HepG2 cells was over 5,000 μg/ml in tested maximum concentration. The effect of REE to protect tacrine-induced cytotoxicity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Radish roots are primarily used as food and food supplement. The beneficial effects of its roots, sprouts, seeds, and leaves include its detoxification in HepG2 cells ( Hanlon et al, 2007 ; Scholl et al, 2011 ) and its hepatoprotective ( Lee et al, 2012 ), antioxidant ( Lugasi et al, 1998 ; Lugasi et al, 2005 ; Beevi et al, 2012 ), anti-inflammatory ( Park and Song, 2017 ), gastroprotective ( Alqasoumi et al, 2008 ; Ahn et al, 2013 ), antimicrobial ( Nehrash, 1961 ; Gutiérrez and Perez, 2004 ), anti-fibrotic ( Asghari et al, 2015 ), anti-obesity ( Kim et al, 2014 ), anti-lipogenic ( Kim et al, 2015b ), and anti-diabetic ( Taniguchi et al, 2007 ; Shukla et al, 2011 ; Banihani, 2017 ) properties. These beneficial effects are often attributed to its sulfur compounds, phenolic compounds, glucosinolates, and flavonoids ( Gutiérrez and Perez, 2004 ; Ediage et al, 2011 ; Shin et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Radish roots are primarily used as food and food supplement. The beneficial effects of its roots, sprouts, seeds, and leaves include its detoxification in HepG2 cells ( Hanlon et al, 2007 ; Scholl et al, 2011 ) and its hepatoprotective ( Lee et al, 2012 ), antioxidant ( Lugasi et al, 1998 ; Lugasi et al, 2005 ; Beevi et al, 2012 ), anti-inflammatory ( Park and Song, 2017 ), gastroprotective ( Alqasoumi et al, 2008 ; Ahn et al, 2013 ), antimicrobial ( Nehrash, 1961 ; Gutiérrez and Perez, 2004 ), anti-fibrotic ( Asghari et al, 2015 ), anti-obesity ( Kim et al, 2014 ), anti-lipogenic ( Kim et al, 2015b ), and anti-diabetic ( Taniguchi et al, 2007 ; Shukla et al, 2011 ; Banihani, 2017 ) properties. These beneficial effects are often attributed to its sulfur compounds, phenolic compounds, glucosinolates, and flavonoids ( Gutiérrez and Perez, 2004 ; Ediage et al, 2011 ; Shin et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The hepatoprotective effects of the radish extract have been recorded by various researchers [36,42,43,44,45,46,47]. Bioactive compounds, such as indole-3-carbinol, 3-[ethoxy- (methylthio)methyl]-2-pyrrolidinethione and 3-(E)-(methylthio)-methylene-2-pyrrolidinethione, present in the radish root and sprouts decreased the severity of fatty liver disease in mouse models [48].…”
Section: Hepatoprotective Effects Of Radishesmentioning
confidence: 99%
“…Therefore, by selecting a wide diversity of raw materials, we were able to investigate dissimilarities in their microbial profiles and identify promising LAB strains in these FVJs. In this study, cherry ( Jacob et al, 2003 ; Chaovanalikit and Wrolstad, 2004 ; Kim et al, 2005 ), white-fleshed pitaya ( Wichienchot et al, 2010 ; Garcia-Cruz et al, 2017 ), white radish ( Hashimoto et al, 2006 ; Lee et al, 2012 ; Kaymak et al, 2015 ), broccoli ( Keck et al, 2003 ; Moreno et al, 2006 ; Berenbaum, 2014 ; Armah et al, 2015 ), and ginger ( Kruth et al, 2004 ; Palatty et al, 2013 ; Daily et al, 2015 ), which have been shown to exhibit a great variety of bioactive characteristics, were chosen as substrates for the isolation of LAB strains and follow-up testing.…”
Section: Introductionmentioning
confidence: 99%